TRANSFORMATION OF THE CONCEPT OF MIDWIFERY IN THE ERA OF DIGITAL HEALTH SERVICES: TRANSFORMASI KONSEP KEBIDANAN DALAM ERA PELAYANAN KESEHATAN DIGITAL - April Artinanda; Ismawati (SOSIOEDUKASI, 2026)
The advancement of digital technology has significantly transformed various sectors, including healthcare. In midwifery practice, digital transformation offers opportunities to improve service quality, accessibility, efficiency, and maternal and neonatal safety. The utilization of technologies such as telemedicine, electronic medical records, maternal and child health applications, and health information systems has shifted midwifery services from conventional approaches to more integrated technology-based care. This study aimed to analyze the transformation of midwifery concepts in the era of digital healthcare services and its implications for service quality.This study employed a quantitative approach with a descriptive analytical design. The sample consisted of 50 midwives working in healthcare facilities. Data were collected using questionnaires and observation sheets. Data were analyzed using univariate and bivariate analyses with the Chi-Square test.The results showed that 72% of respondents had a good understanding of digital healthcare services and 76% had implemented digital technology in midwifery practice. Statistical analysis revealed a significant relationship between digital technology understanding and the quality of midwifery services (p = 0.002). Digital transformation improved communication effectiveness, service documentation, maternal and neonatal monitoring, and clinical decision-making.